Teaching method of designing experiment from the perspective of teacher in power electronics course - Guopeng Zhao (IET Circuits, Devices and Systems)
Abstract In order to solve the problem of lacking active learning and independent problem‐solving ability in the verification experiment, an experimental teaching method of designing experiment from the perspective of the teacher is proposed, in which the roles of students and teachers are changed. Students are made familiar with the platform through a verification experiment in which the teacher gives the experiment guidebook and provides guidance. Then, the target of another experiment is given. The students design the experiment from the perspective of the teacher, and write the experiment guidebook, including the experimental objectives, the experimental contents and the implementation methods. Then the students do the experiment. The power electronics experiment course is taken as an example to introduce the proposed method. The Sinusoidal Pulse Width Modulation (SPWM) inverter circuit experiment is taken as the verification experiment. After the students are familiar with the platform functions, they design a DC motor speed regulation experiment with a full bridge DC‐DC circuit, write a guidebook, and complete the experiment according to the steps in the guide book. Finally, according to the success rate and the correct rate of the results, most students can complete the design experiment from the perspective of the teacher, and the answers to the thinking questions are basically correct. According to the questionnaire survey, the method proposed improves the students' ability of autonomous learning and problem‐solving with good results.